New approaches to textual and image analysis in early Jewish and Christian studies - Schulthess, Sara; Allen, Garrick V.; Dilley, Paul C.; Phillips, Peter M. (Digital biblical studies, 2022)
Intro -- ‎Contents -- ‎1. Textual Approaches, Image Analysis, and Bottom-Up Approaches in Religious Studies (Allen, Dilley and Phillips) -- ‎2. Three Priorities for Digitally-Enabled Research and Teaching in Manuscripts of Biblical Literature (Hanneken) -- ‎3. The Promise and Challenges of Digital Humanities for the Study of Jews and Judaism in Antiquity (Satlow) -- ‎4. The Amsterdam Database of New Testament Conjectural Emendation (Krans) -- ‎5. Mining and Mapping New Testament Metaphors and the Louw-Nida Lexicon (Zwarts) -- ‎6. Applying Cosine Similarity to Paul's Letters: Mathematically Modeling Formal and Stylistic Similarities (Roy and Robertson) -- ‎7. Analyser l'emploi de la terminologie prophétique des manuscrits «non-bibliques» de la Mer Morte en créant une base de données informatique (Minard) -- ‎8. Verse Metrics: Analysing Textual Families of Manuscripts Using a String Alignment Algorithm with a Test Case in the Arabic Gospels (Turnbull) -- ‎9. Let There Be Light: Testing Byzantine Polycandelon and Glass Stemmed Oil Lamp Illumination (Erickson) -- ‎Index of Ancient Sources -- ‎Subject Index.